2014
DOI: 10.1590/s1984-46702014000400005
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dry mass of caddisflies Phylloicus elektoros (Trichoptera: Calamoceratidae) in a Central Amazon stream

Abstract: ABSTRACT. Aquatic invertebrate biomass estimations are often important in ecological and biological studies. Biomass may be determined by regression models between body and case dimensions and dry mass. Using linear, exponential and power regressions we analyzed the relationship between body and case dimensions and the biomass of Phylloicus elektoros Prather, 2003. Furthermore, we used cross-validation to evaluate the predictions of our models and of the models developed for Phylloicus sp. from southeastern Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
(31 reference statements)
1
11
0
3
Order By: Relevance
“…We incubated leaves in the stream to allow natural conditioning before the leaves were broken down by shredders and microorganisms. The stream has dense riparian forest, acidic water (pH = 4.6 ± 0.1), high dissolved oxygen concentration (6.6 ± 0.1 mg l -1 ), low electrical conductivity (10.7 ± 0.4 αS cm -1 ) and mean temperature of 24.5 ± 0.5°C [ 29 ]. The leaves were then cut into discs (14 mm in diameter), avoiding the midrib.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We incubated leaves in the stream to allow natural conditioning before the leaves were broken down by shredders and microorganisms. The stream has dense riparian forest, acidic water (pH = 4.6 ± 0.1), high dissolved oxygen concentration (6.6 ± 0.1 mg l -1 ), low electrical conductivity (10.7 ± 0.4 αS cm -1 ) and mean temperature of 24.5 ± 0.5°C [ 29 ]. The leaves were then cut into discs (14 mm in diameter), avoiding the midrib.…”
Section: Methodsmentioning
confidence: 99%
“…elektoros larvae. This species is an important shredder in Amazon streams [ 29 ]. The larvae are usually abundant in pool mesohabitats [ 30 ], favoring their use in laboratory experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Moretti et al (2009) showed that Phylloicus selected leaves for case-building that were chemically protected againt microbial degradation and consumption by other shredders, but this was dependant on leaf abundance. As a typical and important leaf shredder in Neotropical aquatic ecosystems, Phylloicus has been been the subject of many different kinds of biological and ecological studies, perhaps the most of any caddisfly in the region (e.g., Rincón and Martínez 2006 , Wantzen and Wagner 2006 , Becker et al 2009 , Encalada et al 2010 , Landeiro et al 2010 , Navarro et al 2013 , Vidovix et al 2013 , Guzmán-Soto and Tamarís-Turizo 2014 , Martins et al 2014 , Rezende et al 2015 ).…”
Section: Catalogmentioning
confidence: 99%
“…Phylloicus' larvae are commonly found on submerged leaf litter (Prather, 2003). It is the most abundant shredder taxon in Cerrado (Rezende et al, 2014(Rezende et al, , 2015 and Amazonian headwater streams (Martins, Melo, Gonçalves, & Hamada, 2014;Martins et al, 2015). Phylloicus is a typical shredder and uses leaf litter deposited in pool areas on streams bed to obtain their food and material to case construction (Wantzen & Wagner, 2006).…”
mentioning
confidence: 99%